Drug repurposing: Antimicrobial and antibiofilm effects of penfluridol against Enterococcus faecalis. Issue 1 (20th December 2020) - Zeng, Xianghai; She, Pengfei; Zhou, Linying; Li, Shijia; Hussain, Zubair; Chen, Lihua; Wu, Yong
Abstract: The bacterium Enterococcus faecalis has increasingly attracted global attention as an important opportunistic pathogen due to its ability to form biofilms that are known to increase drug resistance. However, there are still no effective antibiofilm drugs in clinical settings. Here, by drug repurposing, we investigated the antibacterial activity of penfluridol (PF), an oral long‐acting antipsychotic approved by the FDA, against E .  faecalis type strain and its clinical isolates. It was found that PF inhibited the growth of E .  faecalis planktonic cells with the MIC and MBC of 7.81 µg/ml and 15.63 ~ 62.50 µg/ml, respectively. Moreover, PF could significantly prevent the biofilm formation of E .  faecalis at the concentration of 1 × MIC. Furthermore, PF significantly eradicated 24 h pre‐formed biofilms of E .  faecalis in a dose‐dependent manner, with a concentration range of 1 × MIC to 8 × MIC. Here, through the checkerboard method with other tested conventional antibiotics, we also determined that gentamycin, penicillin G, and amikacin showed partial synergistic antibacterial effects with PF. Also, PF showed almost no hemolysis on human erythrocytes. In a mouse peritonitis model, a single dose of 20 mg/kg of PF treatment could significantly reduce the bacterial colonization in the liver (~5‐fold reduction) and spleen (~3‐fold reduction). In conclusion, these findings indicated that after structural optimization, PF has the potential as a new antibacterial agent against E .  faecalis . Abstract : Penfluridol shows effective antimicrobial effects against Enterococcus faecalis in vitro and in vivo. The drug prevents biofilm formation and eliminates mature biofilms.